How is disciplinary literacy addressed in the science classrooms? A Singaporean case study - Tang, Kok-Sing (Australian Literacy Educators' Association, 2016)
Disciplinary literacy is the specific ways of talking, reading, writing, and thinking valued and used by people in a discipline in order to successfully access and construct knowledge in that discipline. This paper reports on a case study of the classroom practices of two physics and two chemistry teachers in Singapore in order to better understand how disciplinary literacy is currently addressed in the teaching of secondary school science. The study found that disciplinary literacy in science teaching was limited to the language aspects of science terminologies and the literacy practice of constructing explanation. Even then, these disciplinary language aspects were only implicitly embedded within the predominant practice of teacher-led talk. Based on these findings, current realities and future possibilities of disciplinary literacy instruction building on science teachers' current teaching practices are discussed.